Agrituristic activities and tourist development inSan Vicente farm. - Narváez Jaramillo, Jenny; Caicedo Rosero, Diego; Benavides Rosales, Hernán; Carvajal Pérez, Luis (SATHIRI, 2019)
Agritourism is a recreational activity included within the modalities of rural tourism, which is articulated one or several phases related to agricultural production, also, agro-industry, crafts and gastronomy, allowing visitors to meet their needs, and new experiences, emotions and knowledge. Then, this research has the objective to determine the agritourism activities in the San Vicente farm for its tourism development. A methodology with a qualitative, non-experimental approach was used, which helped to demonstrate that the resources of the farm can be used for tourism activities. The data collection was carried out with the appropriate techniques and instruments for field research and supported with documentary information. It was determined that the interaction with farm animals, ride and walks are the most preferred activities for the visitors, without detracting from other complementary activities such as photography, observation of agricultural and agroindustry processes; so the agrituristic activities will constitute in a greater measure a way to make efficient the use of all the available resources in the farm to become a new place for recreation, rest, contact with the nature, enjoyment of typical gastronomy, learning about crops and animals’ husbandry, which are activities of interest to visitors.